2004
DOI: 10.2308/aud.2004.23.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Professional Service Fees and Auditor Objectivity

Abstract: This study investigates whether an auditor's objectivity is impaired by nonaudit services or by the level of economic dependence on a client. Like several contemporaneous studies, we use recent mandated proxy statement audit and nonaudit fee disclosures to measure economic dependence and we use discretionary accruals as a surrogate for auditor objectivity. The results in the extant literature are mixed. We provide some explanations for those inconsistent results. First, we replicate the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
0
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(163 citation statements)
references
References 35 publications
10
141
0
12
Order By: Relevance
“…For example, prior studies document no association between the likelihood of auditor qualifications and NAS (Barkess and Simnett, 1994;Craswell, 1999;Craswell, Stokes and Laughton, 2002;DeFond, Raghunandan andSubramanyam 2002 andHay, Knechel andLi, 2006) 2 and audit tenure and NAS (DeBerg, Kaplan and Pany, 1991;Barkess andSimnett, 1994 andHay, Knechel andLi, 2006). 3 Further, although Frankel, Johnson and Nelson (2002) document an association between NAS and both the frequency of reporting a small earnings surprise and discretionary accruals, the results of the study have been found to be sensitive to research design in later studies (Ashbaugh, LaFond, and Mayhew, 2003;Chung and Kallapur, 2003;Larcker andRichardson, 2004 andReynolds, Deis andFrancis, 2004). Cahan, Emanuel, Hay and Wong (2008) find no association in New Zealand between discretionary accruals and either NAS growth rates or the length of time a client has purchased NAS.…”
Section: Takeover Premiums and The Role Of The Target Firm Auditormentioning
confidence: 99%
“…For example, prior studies document no association between the likelihood of auditor qualifications and NAS (Barkess and Simnett, 1994;Craswell, 1999;Craswell, Stokes and Laughton, 2002;DeFond, Raghunandan andSubramanyam 2002 andHay, Knechel andLi, 2006) 2 and audit tenure and NAS (DeBerg, Kaplan and Pany, 1991;Barkess andSimnett, 1994 andHay, Knechel andLi, 2006). 3 Further, although Frankel, Johnson and Nelson (2002) document an association between NAS and both the frequency of reporting a small earnings surprise and discretionary accruals, the results of the study have been found to be sensitive to research design in later studies (Ashbaugh, LaFond, and Mayhew, 2003;Chung and Kallapur, 2003;Larcker andRichardson, 2004 andReynolds, Deis andFrancis, 2004). Cahan, Emanuel, Hay and Wong (2008) find no association in New Zealand between discretionary accruals and either NAS growth rates or the length of time a client has purchased NAS.…”
Section: Takeover Premiums and The Role Of The Target Firm Auditormentioning
confidence: 99%
“…Arruanda adds that it does not necessarily damage auditor independence or the quality of NAS. Reynolds et al (2004) provide evidence that there is no association between NAS and discretionary accruals and conclude that little evidence exists supporting the negative effects of NAS on auditor's independence and objectivity. Lennox (1999) finds that NAS increases auditors' knowledge on clients as well as the probability of discovering problems and mistakes.…”
Section: Provision Of Non-audit Services (Nas)mentioning
confidence: 99%
“…For instance, Reynolds et al, (2004) state that FY 2000 "was characterized by an infatuation with e-commerce, a merger boom, and IPOs tied to the new economy". Finally, this was a period of intense scrutiny of audit firms by the SEC which would check any normal impulses to lower audit quality (Antle et al, 2006;Ruddock et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Frankel et al, (2002) (2003), Francis and Ke (2003), and Reynolds et al (2004) find no consistent evidence when the value of NAS or total fees is the independent variable instead of the ratio measure.…”
Section: Prior Researchmentioning
confidence: 99%